2021
DOI: 10.1093/trstmh/trab119
|View full text |Cite
|
Sign up to set email alerts
|

The role of integrated programs in the prevention of COVID-19 in a humanitarian setting

Abstract: The COVID-19 pandemic has caused a severe depletion to health systems worldwide. In the South Kordofan state, a war-torn humanitarian region in Sudan, the United Nations High Commissioner for Refugees and the WHO Emergencies Programme have led the development of integrated programs for health, peace and rehabilitation by training rapid response teams to strengthen both surveillance system and response capacities, engaging the communities at risk with health education and promotion activities, as well as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Nonetheless, the delay in detecting the emergence of these vectors of arboviral diseases that we report here could be attributed to the partial freeze in environmental and public health services due to the global COVID-19 pandemic [ 51 ]. Therefore, the need for a One Health-integrated surveillance and response system for diseases and their vectors is extreme and urgent [ 50 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the delay in detecting the emergence of these vectors of arboviral diseases that we report here could be attributed to the partial freeze in environmental and public health services due to the global COVID-19 pandemic [ 51 ]. Therefore, the need for a One Health-integrated surveillance and response system for diseases and their vectors is extreme and urgent [ 50 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite many humanitarian settings having robust surveillance, more published reports are needed that describe such systems ( 29 ). A review of the literature covering COVID-19 surveillance found 2 other studies that describe implementation and adaptation to a humanitarian setting, in Yemen and Sudan ( 25 , 30 ). In Sudan, healthcare providers were trained as rapid response teams ( 30 ), whereas in Yemen a community-based surveillance system approach was used ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature covering COVID-19 surveillance found 2 other studies that describe implementation and adaptation to a humanitarian setting, in Yemen and Sudan ( 25 , 30 ). In Sudan, healthcare providers were trained as rapid response teams ( 30 ), whereas in Yemen a community-based surveillance system approach was used ( 25 ). The surveillance system we describe includes elements of community- and healthcare-based surveillance, in which community-based assistants perform contact tracing, identify persons with recent travel history, and refer persons with compatible illness for testing.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to guide interested readers as well as to pool literature related to pneumonia among Sudanese population and for further research prospect, all related articles according to the current search strategy are depicted in (Table 2). Abd El-Raheem et al [28] Characteristics and severity of COVID-19 among Sudanese patients during the waves of the pandemic Abdelmagid et al [29] Acceptability and feasibility of strategies to shield the vulnerable during the COVID-19 outbreak: a qualitative study in six Sudanese communities Abdou et al [30] The coronavirus disease 2019 (COVID-19) vaccination psychological antecedent assessment using the Arabic 5c validated tool: An online survey in 13 Arab countries Abouzid et al [31] Influence of COVID-19 on lifestyle behaviors in the Middle East and North Africa Region: a survey of 5896 individuals Ahmed et al [32] Impact of the COVID-19 pandemic on intimate partner violence in Sudan, Malawi and Kenya Ahmed et al [33] COVID-19 in Sudan Ahmed et al [34] Clinical characteristics, complications, and predictors of outcome of hospitalized adult Sudanese patients with COVID-19 and malaria coinfection in Sudan: A multicenter retrospective cross-sectional study Ahmed et al [35] Controlling the spread of COVID-19 in Sudan with limited resources: a unique community-engaged approach Ali et al [36] The role of integrated programs in the prevention of COVID-19 in a humanitarian setting Aljak et al [37] The first laboratory-confirmed imported infections of SARS-CoV-2 in Sudan Attaallah et al [38] The Prognostic Value of Thrombocytopenia in COVID-19 Pneumonia, Gezira Isolation Centers, Sudan Aung et al [39] Community responses to COVID-19 pandemic first wave containment measures: a multinational study Bara'a et al [40] Coronavirus 2019-like illness and public adherence to preventive measures, Sudan 2020 Deek et al [41] A multi-centric study on validation of the Fear Scale for COVID-19 in five Arabic speaking countries Elagib et al [42] Knowledge, attitude, and practice regarding infection control measures among dental students during COVID-19 pandemic Elhadi et al [43] The formidable task of fighting COVID-19 in Sudan El-Sadig et al [44] Obstacles faced by healthcare providers during COVID-19 pandemic in Sudan El-Sadig et al [45] Impact of COVID-19 on doctors and healthcare providers during the pandemic in Sudan Fahal et al [46] The Mycetoma Research Centre experience during the COVID-19 pandemic: obstacles and beyond Gayawan et al [47] The spatio-temporal pandemic dynamics of COVI...…”
Section: Covid 19 Studiesmentioning
confidence: 99%
“…Controlling the spread of COVID-19 in Sudan with limited resources: a unique community-engaged approach Ali et al [36] 2022…”
mentioning
confidence: 99%